2016
DOI: 10.1177/0022167816681232
|View full text |Cite
|
Sign up to set email alerts
|

Heroism Research: A Review of Theories, Methods, Challenges, and Trends

Abstract: Heroism as an expression of self-actualization and a pinnacle social state is of fundamental interest to humanistic psychology and the field more broadly. This review places the growing discussion on heroic action in a humanistic perspective, as heroism aligns with ethical self-actualization in its highest form, personal meaning making, and social good, and can also involve profound existential costs. This review is organized in four major sections: First, the historical and philosophical underpinnings of hero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 34 publications
1
53
0
1
Order By: Relevance
“…However, future work could advance this work by employing a subliminal priming method, though we return to this point in the General Discussion. This work is consistent with prior work linking heroes and prosociality ( Kinsella et al, 2015a , b ; Franco et al, 2016 ) as well as the association between prosociality and meaning ( Van Tongeren et al, 2016 ). Moreover, it suggests that heroes may serve an important cultural purpose of motivating coalitional behavioral that strengthens the prosociality of a society.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, future work could advance this work by employing a subliminal priming method, though we return to this point in the General Discussion. This work is consistent with prior work linking heroes and prosociality ( Kinsella et al, 2015a , b ; Franco et al, 2016 ) as well as the association between prosociality and meaning ( Van Tongeren et al, 2016 ). Moreover, it suggests that heroes may serve an important cultural purpose of motivating coalitional behavioral that strengthens the prosociality of a society.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has identified numerous methodological challenges with studying heroes, and researchers have suggested that experimental methodology is necessary to advance research in this domain ( Franco et al, 2016 ). Toward that end, we designed two experiments to test our central hypothesis.…”
Section: Overview and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…It marks the end of the centuries old stronghold that mythology, religion and philosophy have had on its observation. This is the second critical interdisciplinary moment in the study of heroism, and the beginnings of a broader global 21 st century heroism movement (Allison, 2015;Efthimiou, 2017a;Franco et al, 2016). But much more work needs to be done, especially between hard science and the humanities.…”
Section: A Brief History Of Heroismmentioning
confidence: 99%